2016
DOI: 10.1017/rdc.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

Supernovae and Single-Year Anomalies in the Atmospheric Radiocarbon Record

Abstract: Single-year spikes in radiocarbon production are caused by intense bursts of radiation from space. Supernovae emit both high-energy particle and electromagnetic radiation, but it is the latter that is most likely to strike the atmosphere all at once and cause a surge in 14C production. In the 1990s, it was claimed that the supernova in 1006 CE produced exactly this effect. With the 14C spikes in the years 775 and 994 CE now attributed to extreme solar events, attention has returned to the question of whether h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
3
28
1
Order By: Relevance
“…The deviation in terms of standard deviations (dev σ) is calculated as ( 14 C Museum and prepared and analyzed at AARAMS like the wood pieces used in this study. Some disagreements between the AD 1000 dataset of this study and the data by Fogtmann-Schulz et al 2017 1995Dee et al 2017Güttler et al 2013Menjo et al 2005Miyake et al 2013Miyake et al 2014 IntCal13 T−filter F=3…”
Section: Methodscontrasting
confidence: 53%
See 1 more Smart Citation
“…The deviation in terms of standard deviations (dev σ) is calculated as ( 14 C Museum and prepared and analyzed at AARAMS like the wood pieces used in this study. Some disagreements between the AD 1000 dataset of this study and the data by Fogtmann-Schulz et al 2017 1995Dee et al 2017Güttler et al 2013Menjo et al 2005Miyake et al 2013Miyake et al 2014 IntCal13 T−filter F=3…”
Section: Methodscontrasting
confidence: 53%
“…records have also been used to search for similar excursions in the atmospheric 14 C content that may be caused by near-Earth supernova explosions, but so far no clear indications of such an event have been found (Damon et al 1995;Menjo et al 2005;Dee et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…If M12 was caused by a supernova, a candidate supernova should exist, but observations spanning several hundred years before AD 775 record no such event. Supernovae emit both high-energy particles and gamma rays, but high-energy particles from supernova have sufficient energy spread that extended arrival times spanning at least 10 yr would be expected (Gehrels 2003;Dee et al 2017) *Corresponding author. Email: jsouthon@uci.edu.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that analysis of cosmogenic isotopes may be the only available proxy for historic extreme SEP events (Usoskin et al, 2006;Miyake et al, 2012Miyake et al, , 2013Usoskin et al, 2013;Herbst et al, 2015;McCracken & Beer, 2015;Dee et al, 2016). This would be a hugely valuable data source in constraining the limits of extreme SEP events, which have quite poor statistics over the space age , and are critical for assessing the hazards and risks to our continuing exploration and development of the solar system (Cannon et al, 2013), especially for manned missions.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been argued, both through observations and physical modelling, that extreme SEP events may measurably perturb the 14 C and 10 Be cosmogenic isotope records (Usoskin et al, 2006;Miyake et al, 2012Miyake et al, , 2013Usoskin et al, 2013;Herbst et al, 2015;McCracken & Beer, 2015;Dee et al, 2016). Therefore, cosmogenic isotopes may provide the only viable proxy record for historic SEP fluxes.…”
Section: Introductionmentioning
confidence: 99%